Room Temperature Deposition of SiNx and Plasma Polymer Layers for Flexible Multilayer Barrier Films by Plasma Enhanced Chemical Vapor Deposition Processes - Yong, Sang Heon; Ahn, Hyung June; Kim, Sun Jung; Park, Jang Soon; Kwon, Sungyool; Cho, Sung Min; Jung, Donggeun; Chae, Heeyeop (Nano : brief reports and reviews, 2018)
In this work, silicon nitride (SiNx) films were deposited on plastic substrates at room temperature close to 30 ∘ C on polyethylenenaphthalate (PEN) films in an inductively coupled plasma (ICP) reactor with trisilylamine (TSA, N(SiH 3 ) 3 ) precursor and ammonia for flexible moisture barrier films. Moisture barrier property is improved as SiNx layer gets thicker, but cracks are found at thicker films above 300 nm or more. And the barrier performance of the thicker layers is degraded significantly. In order to improve both flexibility and barrier property, plasma polymer (PP) layers were deposited at room temperature and introduced between the SiNx layers. The water vapor transmission rate (WVTR) of a single SiNx film, 6 . 3 × 1 0 − 3 g/(m 2 ⋅ day ), is reduced to 1 . 3 × 1 0 − 3 g/(m 2 ⋅ day ) with SiNx/PP/SiNx/PP/SiNx alternating five-layer structure. After 1000 times bending in 1.5 cm of bending radius, the WVTR increases by 41% with five-layer structure, while that of single-layer structure increases by 69%. This work demonstrated that the SiNx and PP layers can be deposited at room temperature for flexible moisture barrier films. Flexible SiNx/plasma polymer multilayer moisture barrier was deposited by plasma enhanced chemical vapor deposition processes at room temperature close to 30 ∘ C. The trisilylamine and NH3 were used to form SiNx in an inductively coupled plasma reactor. The water vapor transmission rate of 1 . 3 × 1 0 − 3 g/(m 2 ⋅ day ) was achieved with a five-layer structure, and this is 79% lower than a single SiNx. Less change in WVTR was observed after 1000 bending at 1.5 cm radius with the five-layer structure.